Ecological specialization and niche overlap of subterranean rodents inferred from DNA metabarcoding diet analysis - Lopes, Carla Martins; De Barba, Marta; Boyer, Frederic; Mercier, Celine; Galiano, Daniel; Kubiak, Bruno Busnello; Maestri, Renan; Silva da Silva Filho, Pedro Joel; Gielly, Ludovic; Coissac, Eric; Ochotorena de Freitas, Thales Renato; Taberlet, Pierre (Wiley-Blackwell, 2020)
Knowledge of how animal species use food resources available in the environment can increase our understanding of many ecological processes. However, obtaining this information using traditional methods is difficult for species feeding on a large variety of food items in highly diverse environments. We amplified the DNA of plants for 306 scat and 40 soil samples, and applied an environmental DNA metabarcoding approach to investigate food preferences, degree of diet specialization and diet overlap of seven herbivore rodent species of the genusCtenomysdistributed in southern and midwestern Brazil. The metabarcoding approach revealed that these species consume more than 60% of the plant families recovered in soil samples, indicating generalist feeding habits of ctenomyids. The family Poaceae was the most common food resource retrieved in scats of all species as well in soil samples. Niche overlap analysis indicated high overlap in the plant families and molecular operational taxonomic units consumed, mainly among the southern species. Interspecific differences in diet composition were influenced, among other factors, by the availability of resources in the environment. In addition, our results provide support for the hypothesis that the allopatric distributions of ctenomyids allow them to exploit the same range of resources when available, possibly because of the absence of interspecific competition.
Keywords: allopatry; Ctenomys; environmental DNA; food resources; interspecific competition; metabarcode